2014
DOI: 10.1021/pr500818d
|View full text |Cite
|
Sign up to set email alerts
|

The Human Colostrum Whey Proteome Is Altered in Gestational Diabetes Mellitus

Abstract: Proteomics of human milk has been used to identify the comprehensive cargo of proteins involved in immune and cellular function. Very little is known about the effects of gestational diabetes mellitus (GDM) on lactation and breast milk components. The objective of the current study was to examine the effect of GDM on the expression of proteins in the whey fraction of human colostrum. Colostrum was collected from women who were diagnosed with (n = 6) or without (n = 12) GDM at weeks 24–28 in pregnancy. Colostra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 47 publications
(83 reference statements)
3
32
0
Order By: Relevance
“…LC separation was done on a Waters Nano Acquity UHPLC (Waters Corporation) with a Proxeon nanospray source. Mass spectra was collected on an Orbitrap Q Exactive Plus mass spectrometer (Thermo Fisher Scientific) in a data-dependent mode with one MS precursor scan followed by 15 MS/MS scans as previously described [11]. Detailed information on instrument parameters and mass spectra collection is provided in the Additional file 1: Supplemental materials and methods (1a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC separation was done on a Waters Nano Acquity UHPLC (Waters Corporation) with a Proxeon nanospray source. Mass spectra was collected on an Orbitrap Q Exactive Plus mass spectrometer (Thermo Fisher Scientific) in a data-dependent mode with one MS precursor scan followed by 15 MS/MS scans as previously described [11]. Detailed information on instrument parameters and mass spectra collection is provided in the Additional file 1: Supplemental materials and methods (1a).…”
Section: Methodsmentioning
confidence: 99%
“…A conservative approach was used to overview data quality metrics in order to identify the most robust proteomic measurements for downstream statistical and multivariate analyses [11]. A total of 799 high quality protein measurements (spectral counts) based on absence of abundant missing zeros, replicate precision, protein sequence coverage and annotation to known genes were selected for further statistical and multivariate analyses.…”
Section: Methodsmentioning
confidence: 99%
“…12,66 Together, the proteins experimentally confirmed here will serve to greatly improve publicly available databases and annotations. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 22…”
mentioning
confidence: 87%
“…Among the few studies that have been conducted among women with GDM, one of them showed that colostrum of GDM mothers presented an altered whey proteome [36]. Another study showed no major difference regarding amino acid content of GDMBM when compared to BM of nondiabetic women [37].…”
Section: Gestational Diabetes Mellitus and Breast Milk Compositionmentioning
confidence: 99%